Pet Abuse and Family Violence – Phenomenology, Relations and State Reaction - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
In a society oriented towards biocentrism, struggling to overcome dualism between humankind and nature, animals are treated as beings equal to people with their own values. A changed ethical attitude towards animals, particularly pets, has affected their legal status and their position in the community. Nowadays, numerous states have laws dedicated to the protection of animals, whereas research shows that owners treat their pets as family members. At the same time, pets’ participation in family activities has its negative side – they often share the destiny of the victims of family violence. It has been confirmed that violence against family members and animal cruelty or abuse overlap, so the author of this paper analyses the phenomenology of these two forms of violence and highlights their roles as predictors, indicators or consequences. After a brief overview of state reaction to these forms of violence in Serbia, the author draws conclusions and recommendations for their noticing, sanctioning and prevention.